Reducing Salesperson Turnover Intentions via Organizational Market Orientation and Selective Hiring: A Job Demand-Resources Approach. Issue 3 (2nd October 2022) - Fleming, David E.; Artis, Andrew B.; Harris, Eric G.; Fergurson, J. Ricky; Askew, Matthew A
ABSTRACT: Purpose: This study is designed to respond to repeated calls for research on sales person retentionby building upon a mature research stream to identify ways to reduce turnover in boundary spanning employees and the resultant effect it has on organizational productivity. Specifically, this research draws on the Job Demands-Resources model to explore the effect of employee perceptions of firm market orientation as a way to reduce role stressors and subsequently turnover intentions. It also looks at employee traits that may serve as a buffer to the role stress to turnover intentions link and can be part of the hiring selection process (in this case grit). In so doing, this research uses a sample of early career salespeople to examine the effects of a firm's market orientation (MO) and selective hiring for specific traits (level of grit) on a salesperson's intention to quit using Job Demand-Resources as a framework. Design/Methodology/Approach: The authors utilized a questionnaire to collect data from a sample consisting of 260 respondents who were employed full-time and worked in either B2B or B2C sales as boundary-spanning employees. The measures utilized in this study have been used in previous research and have demonstrated acceptable reliability and validity. Analysis of the latent constructs was conducted using PLS-SEM. The model was assessed as specified in the hypotheses and was estimated using the PLS algorithm to obtain path coefficient estimates. Findings: Findings suggest that organizations can benefit internally from strong MO by mitigating stressors placed on boundary-spanning employees. Those who perceived strong MO in their employer experienced more clearly defined roles, which led to decreased role ambiguity. These increased levels of job satisfaction, which reduced turnover intention. Additionally, Grit appears to only moderate the link between role conflict and job satisfaction, which suggests that grit can serve as an additional resource salespeople can tap into in response to the demands of role stressors thereby reducing their likelihood of leaving their positions. Research Implications: In this research, inclusion of market orientation as an antecedent to role stressors in the Job Demands-Resources model expands the conceptualization of the construct as it relates to salespeople in that market orientation is something the firm can control directly. This opens research opportunities to use this model in the sales literature. In addition, the job-demands-resources model expands the role of grit beyond positive psychology to be viewed as a resource in stressful situations and puts the role of grit into a theoretical framework for use in business contexts. As such, the current work suggests that the grit scale can be used to replace measures used for similar constructs such as tenacity. Practical Implications: This research suggests that role ambiguity can be reduced by the presence of a market orientation. This reduction in role ambiguity leads to an increase in job satisfaction which leads to reduced turnover intention. Thus, this study indicates that there may be a cost-saving benefit (e.g. recruiting and retention efforts, lost sales, etc.) that accrues to firms with a market orientation due to reduced salesperson turnover via role perceptions. This supports that the idea that organizations can benefit from market orientation not only externally, but also internally in terms of mitigating stressors placed on boundary-spanning employees. Therefore, companies should push for adoption of market orientation in order to alleviate some key role stressors placed on their salespeople in addition to the already established benefits from external customers. The link between grit, job satisfaction, and turnover intentions is another positive finding. As expected, job satisfaction helps reduce turnover intentions; however, the relationship is moderated by grit in such a way that people with higher grit show a weaker link between job satisfaction and turnover intentions while those with lower levels of grit show a stronger link between job satisfaction and turnover intentions. This raises human resource issues in the hiring process: human resource managers should work to identify salespeople with high levels of grit in order to better minimize turnover intentions given the cost of turnover to organizations. Originality: This research expands existing research by examining the effects of a firm's market orientation (MO) and selective hiring for specific traits (level of grit) on a salesperson's intention to quit using Job Demand-Resources as a framework Combining these two literature streams – market orientation and salesperson grit – is novel and will inspire new thinking and foster new insights. This study serves as a starting point for future research to examine firm controllable resources (market orientation) along with employee traits that can act as a buffer (grit) when resources are scarce.